Dampak Penggunaan Gadget Terhadap Minat Belajar PPKn Siswa di SMK Dwijendra Denpasar Tahun Pelajaran 2019/2020 - I Made Sutika; Putu Ronny Angga Mahendra; Stevin Ira Aricindi Gah (Universitas Pendidikan Ganesha, 2020)
Gadgets have become a part of student’s life, so the exsistence of gadgets causes both positive and negative effect. The gadget can give positive effect such as efficiency on education development, simplification of finding information and communication, and it makes students technologi literate.This study aimed at determining the effect of using gadgets on students Pancasila and Civics Education learning interest in grade XI of Hospitality at SMK Dwijendra. Furthermore, this study also aimed at determining students’ learning interest of grade XI of Hostitality at SMK Dwijendra Denpasar.This research was conducted in grade XI of Hospitality at SMK Dwijendra Denpasar. This type of research was descriptive using a qualitative approach, the subjects of this study were students. The data collection techniques were observation techniques, interview techniques, and documentation. The data were analyzed using inductive data analysis techniques, with steps including data collection, and drawing conclusion. The findings showed that the effect of using gadgets on students Pancasila and Civics Education learning interest in grade XI of Hospitality at SMK Dwijendra were 1) positive effect, namely technology-based learning resourcs, increasing knoledge about technological progress; 2) negative effect, namely lack of enthuisasm for student learning, social stroge, undisciplined; 3) due to gadget addiction, students were no longer interested in learning achievement decreased.